2017
DOI: 10.1002/smtd.201700220
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Surface Modification of Materials Based on Transition‐Metal Dichalcogenides for Biomedical Applications

Abstract: With the rapid development of nanotechnology, the emerging transition‐metal dichalcogenides (TMDCs) have become one of the most promising inorganic nanomaterials for medical applications due to their distinctive structures and properties. TMDCs with different sizes and morphologies exhibit unique structural advantages, as well as versatile properties. However, concerning their practicability for biomedical applications, routes toward their synthesis and chemical/physical functionalization for biosystem applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 173 publications
(289 reference statements)
0
63
0
Order By: Relevance
“…Future advancements in combination therapy between gas therapy and other treatment are expected to enhance the efficacy of gas therapy and simultaneously reduce the side effects of a single treatment. Last but not least, before these emerging delivery strategies can be used in clinical therapy, their physiological dispersibility and stability, biocompatibility, biodistribution as well as biosafety should be thoroughly evaluated by systematic studies . More worthy of mention, in order to achieve clinical translation of CO therapy, multidisciplinary collaboration would be essential.…”
Section: Resultsmentioning
confidence: 99%
“…Future advancements in combination therapy between gas therapy and other treatment are expected to enhance the efficacy of gas therapy and simultaneously reduce the side effects of a single treatment. Last but not least, before these emerging delivery strategies can be used in clinical therapy, their physiological dispersibility and stability, biocompatibility, biodistribution as well as biosafety should be thoroughly evaluated by systematic studies . More worthy of mention, in order to achieve clinical translation of CO therapy, multidisciplinary collaboration would be essential.…”
Section: Resultsmentioning
confidence: 99%
“…During the past years, much effort was devoted to the exploration of TMDs‐based hybrid nanostructures for biomedical applications, including biological imaging, cancer therapy, antibacterial treatment, biosensing, and drug delivery . TMDs nanosheets not only had large specific surface area to load various biomolecules, medicines, and functional building blocks but were also biocompatible with negligible cytotoxicity . Despite these merits, the main challenge to constructing reliable TMDs‐based hybrid nanostructure for biomedical applications was building strong interfacial interactions because of the chemical inertness of TMDs.…”
Section: Coordination‐driven Assembly Based On Tmdsmentioning
confidence: 99%
“…Recent literature also witnessed an increasing interest in employing graphene analogs such as thin‐layer transition metal dichalcogenides (TMDs) as antibacterial materials. Thin‐layer molybdenum disulfide (MoS 2 ) that belongs to the thin‐layer TMDs family has been extensively employed for biomedical applications mainly due to the following reasons: 1) Its double‐sided S layer sandwiching the Mo layer offers scope for effective covalent or noncovalent modification with functional molecules; 2) Its unique optical properties make possible wavelength‐tunable, light‐driven photodynamic and photothermal therapies; 3) Recent long‐term in vivo studies suggested its low toxicity and biocompatibility for live animals . Bearing these merits in mind, here we report the construction of thin‐layer MoS 2 ‐based multivalent glycosheets for the targeted, light‐driven therapy (i.e., targeted bacterial immobilization, NIR‐light‐driven thermal release of antibiotics, and white light–driven reactive oxygen species [ROS] production— Figure ) of multidrug‐resistant P. aeruginosa on wounds.…”
Section: Introductionmentioning
confidence: 99%